Environmental Performance and Financial Performance on Greenwashing Practices - Maria Paramastri Hayuning Adi; Patricia Paramitha Suci; Irfana Rahma Dzikria (Universitas Teknologi Yogyakarta, 2026)
Greenwashing has emerged as an increasingly critical concern as stakeholders demand stronger corporate environmental accountability, particularly within the energy sector given its substantial environmental footprint. The disparity between environmental disclosure and actual environmental performance risks misleading stakeholders and undermining the effectiveness of climate-related policies. This study examines the effects of environmental performance and financial performance on greenwashing practices, with particular attention to the moderating role of financial performance in this relationship. The research gap addressed here stems from inconsistent findings in prior studies and the scarcity of empirical evidence from the Indonesian context. Employing a quantitative approach, this study draws on secondary data from energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. A purposive sampling technique yielded a final sample of 36 companies, corresponding to 108 firm-year observations. Data were analyzed using panel data regression with an interaction model in Stata. Greenwashing was measured via a greenwashing index, environmental performance was proxied by environmental capital expenditure relative to revenue, and financial performance was assessed using Return on Assets (ROA). The results indicate that environmental performance has a positive and significant effect on greenwashing practices, whereas financial performance exerts no significant direct effect. Notably, financial performance significantly moderates the relationship between environmental performance and greenwashing: the negative coefficient of the interaction term suggests that stronger financial performance attenuates the positive association between environmental performance and greenwashing behavior. Based on these findings, this study recommends enhancing the quality of sustainability disclosure and adopting output-based environmental performance indicators in future research.